Dysregulation of lipid metabolism, energy production, and oxidative stress in myalgic encephalomyelitis/chronic fatigue syndrome, Gulf War Syndrome and fibromyalgia - Davis, Leah; Higgs, Maisy; Snaith, Ailsa; Lodge, Tiffany A.; Strong, James; Espejo-Oltra, Jose A.; Kujawski, Sławomir; Zalewski, Paweł; Pretorius, Etheresia; Hoerger, Michael; Morten, Karl J. (Frontiers in Neuroscience, 2025)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS), Gulf War Syndrome (GWS), and Fibromyalgia (FM) are complex, chronic illnesses with overlapping clinical features. Symptoms that are reported across these conditions include post-exertional malaise (PEM), fatigue, and pain, yet the etiology of these illnesses remains largely unknown. Diagnosis is challenging in patients with these conditions as definitive biomarkers are lacking; patients are required to meet clinical criteria and often undergo lengthy testing to exclude other conditions, a process that is often prolonged, costly, and burdensome for patients. The identification of reliable validated biomarkers could facilitate earlier and more accurate diagnosis and drive the development of targeted pharmacological therapies that might address the underlying pathophysiology of these diseases. Major driving forces for biomarker identification are the advancing fields of metabolomics and proteomics that allow for comprehensive characterization of metabolites and proteins in biological specimens. Recent technological developments in these areas enable high-throughput analysis of thousands of metabolites and proteins from a variety of biological samples and model systems, that provides a powerful approach to unraveling the metabolic phenotypes associated with these complex diseases. Emerging evidence suggests that ME/CFS, GWS, and FM are all characterized by disturbances in metabolic pathways, particularly those related to energy production, lipid metabolism, and oxidative stress. Altered levels of key metabolites in these pathways have been reported in studies highlighting potential common biochemical abnormalities. The precise mechanisms driving altered metabolic pathways in ME/CFS, GWS, and FM remain to be elucidated; however, the elevated oxidative stress observed across these illnesses may contribute to symptoms and offer a potential target for therapeutic intervention. Investigating the mechanisms, and their role in the disease process, could provide insights into disease pathogenesis and reveal novel treatment targets. As such, comprehensive metabolomic and proteomic analyses are crucial for advancing the understanding of these conditions in-order to identify both common, and unique, metabolic alterations that could serve as diagnostic markers or therapeutic targets.